Financial Literacy and Saving Behavior of University Students (A Case Study of BBA Students of Uganda Christian University) - Gloriah Shida (Uganda Christian University, 2024)
This study delves into how BBA students at Uganda Christian University (UCU) handle their finances and saving habits. It aims to shed light on how well these students understand money management and how this knowledge influences their saving practices. By looking at the experiences of BBA students from 2022 to 2024, the research seeks to uncover what factors shape their financial behaviours and the challenges they encounter. Ultimately, it aims to provide insights into how students can improve their financial literacy and better manage their savings. The research took a descriptive quantitative approach to explore how students at Uganda Christian University manage their finances and what influences their saving habits. Out of a total of 160 students, 113 were randomly chosen to participate in the study. To collect data, the researchers used self-administered questionnaires that asked students about their financial knowledge and saving practices. The study revealed that while BBA students at Uganda Christian University have a solid understanding of budgeting, savings accounts, and credit management, there’s a clear gap when it comes to investment knowledge. Most students are between 18 and 23 years old, and the gender distribution is nearly balanced. This indicates that students are confident in handling daily financial tasks but less informed about investment strategies. To address this, the study suggests several improvements. It recommends adding specialized workshops and courses focused on investment to the curriculum. Incorporating financial literacy more deeply into core courses and creating peer-led programs could also boost students’ financial skills. Moreover, offering pre-loan counselling and running savings challenges might help improve their financial behaviours. The study recognizes some limitations, such as the small sample size and the potential biases of self-reported data, which might not fully represent the entire student body. It suggests that future research could broaden its scope by including students from different programs and exploring new financial tools and practices to better understand financial literacy in today's digital world.